Pengaruh Employee Engagement dan Organizational Citizenship Behavior (OCB) Terhadap Kepuasan Kerja (Studi Kasus Pada Karyawan Angrumba) - Nurjiddah M Hi Yusuf; Budi Wahono; Eris Dianawati (UNIVERSITAS ISLAM MALANG, 2022)
Abtract This study aims to determine the effect of employee engagement and organizational citizenship behavior (OCB) on job satisfaction. The population in this research is an employee of angrumba madiun regency. The sample used is as many as 36 employees. Data was taken by using a questionnaire method. The data analysis method used is simple regression analysis with the help of SPSS software version 14 (Statistical Products and Service Solutions version 14). The test data used is a partial hypothesis test (t). The results showed that partially employee engagement variable (sig = 0.048) and organizational citizenship behavior (OCB) (sig = 0.001) had an effect on job satisfaction. Keywords: Employee Engagement, Organizational Citizenship Behavior (OCB) And Job Satisfaction